Theologische ‚Wahrheit‘ im Prozess der Modernisierung: Bemerkungen zu August Dorner und Wilhelm Herrmann - Wittekind, Folkart (Interdisciplinary journal for religion and transformation in contemporary society, 2022)
The essay compares August Dorner’s and Wilhelm Herrmann’s usage of the concept of truth. Truth is connected to individuality and collective consciousness. Describing the differences in terms of theological history leads to the question which function the respective usage fulfils and how the perception of theology changes accordingly. Wilhelm Hermann’s theology is thus characterized as an attempt to use the concept of truth to advance a constitutive-reflexive modernization of theology.